Spermatozoa binding to bovine oviduct cells: the influence of the endocrine milieu on the effectiveness of the binding test in vitro - Souza, Paula Renata Cortat de (2024)
Field fertility analysis of bulls is time-consuming and with low accuracy. In addition, mimicking gamete maturation time is a challenge in the application of reproductive biotechnologies. Some in vitro studies have demonstrated the ability of spermatozoa to bind to bovine oviductal epithelial cells (BOEC) before fertilization. This binding assay has shown a high correlation with fertility; however, there are no reports in the literature of this technique being performed in bovine models at known stages of the estrous cycle, i.e., the time compatible with fertilization. Therefore, the present study aims to characterize the best OEC culture model and to validate the binding assay in bulls. With this purpose, two experiments will be performed. In the first study, oviducts obtained from a slaughterhouse were collected and the isthmus region was used. Samples were separated according to the presence of a corpus luteum (CL) or dominant follicle (DF). In experiment 2, 7 cows (Bos indicus) with DF ≥ 10 mm received 16.8 µg buserelin acetate (GnRH) on day 0. Ovulation was confirmed on day 3 and cows were assigned to receive two treatments: CL group (n = 5) or DF group (n = 5). In the DF group, on day 3, cows received a new P4 device (0.5 g) plus 2 mg estradiol benzoate. On day 11 and 13 0.5 mg cloprostenol were given, concomitant with P4 withdrawal on day 13. Ultrasound was performed on day 0, 3, 11, and 13 to guarantee the presence of a 14-d CL (CL group) or a pre-ovulatory follicle (DF group). The slaughter was performed on D14 with blood collection to analyze circulating P4. In both experiments, the isthmic region of the oviduct was dissected and divided into four groups according to the location of the oviduct relative to the ovarian structures present, i.e., CL or DF (ipsilateral or contralateral), forming four groups: CL-contra, CL-ipsi, DF-contra, and DF-ipsi. In both experiments, follicular fluid (FF) was collected for analysis of estradiol and progesterone concentrations. Cells were cultured in TCM-199 medium for 24 hours to form explants. After this process, the explants were divided into drops (one for each group) and co-incubated with 1x105 motile spermatozoa per mL. A pool of semen straws from three bulls with known field fertility was used. In addition, sperm motility was assessed by the CASA system, and plasma and acrosomal membrane integrity was assessed by fluorescence microscopy. The number of bound sperm per mm of cell explant was evaluated after 0.5, 12, and 24 hours of co-incubation. Hormonal measurements were performed by chemiluminescence. Plasma progesterone was higher in the CL groups, as expected, and P4 from follicular fluid was higher in CL-Ipsi in both studies. Estradiol was higher in DF-Ipsi in experiment 2. Regarding the sperm binding per mm of explant, the CL-Ipsi group had the lowest binding at all analysis times. In conclusion, the endocrine environment influences the ability of sperm to bind to BOEC. Therefore, the best in vitro model to evaluate sperm binding as a strategy to evaluate fertility is using the oviduct from tracts with DF and without CL.